PENGUKURAN PERFORMANSI RANTAI PASOK PADA INDUSTRI BATIK TIPE PRODUKSI MAKE-TO-STOCK DENGAN MENGGUNAKAN MODEL SCOR 11.0 DAN PEMBOBOTAN AHP (Studi Kasus Batik Gunawan Setiawan, Surakarta) - Taufiq Immawan; Chandra Yuda Pratama (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Batik is Indonesia's cultural heritage has been recognized through this UNESCO.Hal impact increased competition among industry batik.Salah an effort in order to win the competition is to determine the performance of supply chain industry batik.Pada this study measured the performance of the supply chain of industrial production type Make-batik toStock, case studies Batik Gunawan Setiawan using the SCOR model and weighting 11.0 AHP.Tujuan this study was to determine the performance of supply chain at Batik Gunawan Setiawan. The results of this study, the measurement of each attribute using the SCOR model 11.0 to 98.17% batik Reliability, Responsiveness 64.40 today, 14:39 today Agility, Cost Rp. 185 173. 537, -, and Asset Management 20:15 today. The measurement results batik 97.65% Reliability, Responsiveness 40.78 days, 14.70 days Agility, Cost Rp. 273 292 491, -, and Asset Management 18:04 today. And the measurement results batik combined 97.60% Reliability, Responsiveness 60.19 days, 17.61 days Agility, Cost Rp. 271 219 750, -, and Asset Management 21:17 today. The average results of measurement are included in the category of Average. Large attribute weights using AHP ie Reliability 0079, responsivenes 0194, 0035 Agility, Cost 0689, and 0003 Asset Management. Weights tge ie Cost. The results of the industry supply chain performance measures Batik Gunawan Setiawan ie 68.79% included in the category of Average. Recommendations are given is to eliminate the patterning process of batik as an Innapriorate processing. Reducing the waiting time from the process of negotiation and supplier selection colouring. Doing to improve the performance of the procurement of raw materials.